Gender affirming pathways in Italy between law, health issues and social considerations - Davide Costa (Science & Philosophy, 2023)
The transgender experience predicts that the gender affirming pathway is undertaken. The gender affirmation process is not mandatory, and the process is not the same for all people. Affirmation of gender is a social determinant of transgender and gender diverse (TGD) health, but which also has a multidimensional structure: social, legal, psychological, and medical. At this point, however, it is necessary to understand the type of pathway that TGD people can undertake in Italy, so the purpose of this paper is to make the articulation of the pathway known and explicit, trying to detect the sociological aspects and the impacts that the various components of the gender affirming pathway require. The gender affirming pathway in Italy is characterized by many critical issues: it is focused on the affirmation of medical, legal, and psychological dimensions; however, the affirmation of social gender is also important to promote their integration into society, their health and general well-being. In conclusion, it is necessary to develop and implement research and concrete impacts of social gender affirmation, the potential of which is to reduce inequalities, in general, and health, which negatively impact the Italian TGD individuals.